PERFORMANCE ENHANCEMENT OF SOLAR CHIMNEY POWER PLANT SUPPLEMENTED WITH EXTERNAL HEAT SOURCE - AURYBI, MOHAMMED ABDULNABI (2018)
This research investigates the integration of wasted energy from flue gases to enhance a conventional solar chimney performance to generate power for 24 hours. A hybrid solar chimney is a modified system equipped with flue channels as a heat exchanger below the collector cover